Analysis of Customer Preferences and Satisfaction toward Sharia Bank Services in Indonesia during the Covid-19 Pandemic - Riduwan Riduwan; Akhmad Arif Rifan; Muhammad Shulthoni; Muhammad Irwan Ariffin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
Islamic banks are one of the financial industries affected by the covid 19 pandemic. The inability to pay their obligations to Islamic banks and deposit withdrawals directly impacts the decline in customer business. This condition increases the risk of Islamic banks so that the ability of Islamic banks is needed to maintain customer loyalty. This study aims to analyze customer preferences and satisfaction with Islamic banking services during the pandemic.The data analyzed is primary data with 308 Islamic bank customers as respondents. Determination of the sample using the purposive sampling method with the criteria of the management of Islamic social organizations has been a customer since before the pandemic and made transactions during the pandemic. The data analysis uses the Importance Performance Analysis (IPA) method with the Carter approach (Compliance, Assurance, Responsiveness, Tangible, Empathy and Reliability).The results showed that compliance and assurance have a high level of performance with high preferences and satisfaction. Meanwhile, people's preferences are low, and satisfaction is low because their performance is also low in the tangible and reliability aspects. Another finding is that customers have high preferences but low satisfaction because their performance is typical responsiveness, and people have low preferences. Still, high satisfaction lies in the reliability and empathy aspects.